1994
DOI: 10.1021/bi00209a011
|View full text |Cite
|
Sign up to set email alerts
|

A Model Structure of the Muscle Protein Complex 4Ca2+.cntdot.Troponin C.cntdot.Troponin I Derived from Small-Angle Scattering Data: Implications for Regulation

Abstract: We report here a model structure for 4Ca2+.troponin C.troponin I derived from small-angle X-ray and neutron scattering data using a Monte Carlo modeling method. In this model, troponin I appears as a spiral structure that wraps around 4Ca2+.troponin C which adopts an extended dumbbell conformation similar to that observed in the crystal structures of troponin C. The troponin I spiral has the approximate dimensions of an alpha-helix and winds through the hydrophobic "cups" in each globular domain of troponin C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
92
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 42 publications
11
92
2
Order By: Relevance
“…Although the specific structural features of this extension cannot be deduced from the low-resolution neutron models, the novel finding of this structural change in sTnI has laid a foundation for further high-resolution studies. 15,[63][64][65] All optimized SANS-derived models point to a similar shape for sTnC, that of a fully extended dumbbell shape in both Ca 21 -free and Ca 21 -bound states, consistent with previous interpretations 48,49 as opposed to the somewhat more compact conformation observed in the cTn crystal structure 60 and SANS models for cTn. 50,51 In the SANS-derived model for sTn, the N-terminal domain of Ca 21 -bound sTnC rotates more than 1008 away from the position seen in the crystal structure.…”
Section: Probing the Structures Of Muscle Regulatory Proteins 509supporting
confidence: 84%
See 2 more Smart Citations
“…Although the specific structural features of this extension cannot be deduced from the low-resolution neutron models, the novel finding of this structural change in sTnI has laid a foundation for further high-resolution studies. 15,[63][64][65] All optimized SANS-derived models point to a similar shape for sTnC, that of a fully extended dumbbell shape in both Ca 21 -free and Ca 21 -bound states, consistent with previous interpretations 48,49 as opposed to the somewhat more compact conformation observed in the cTn crystal structure 60 and SANS models for cTn. 50,51 In the SANS-derived model for sTn, the N-terminal domain of Ca 21 -bound sTnC rotates more than 1008 away from the position seen in the crystal structure.…”
Section: Probing the Structures Of Muscle Regulatory Proteins 509supporting
confidence: 84%
“…Upon Ca 21 binding to the regulatory sites of TnC, TnI was observed to undergo a large-scale structural change resulting in a more compact structure with a $ 10% decrease in the radius of gyration R g and a $ 9% increase in the apparent cross-sectional radius of gyration (R c ). By modelling TnI as a two-domain molecule represented by oblate and prolate ellipsoids containing 65% and 35% of the mass, respectively, these researchers concluded there was a decrease in the center-of-mass separation of these domains of $ 15 Å upon Ca 21 addition, a strong indication that TnI acts as a molecular switch consistent with the mechanism proposed by Olah et al 46 Of note, sTnI in the ternary complex 49 was found to be more compact than was observed in for the binary complex, 46,48 suggesting interactions with sTnT were important in determining the structure of sTnI in the complex. Further development of ideas about the proposed Ca 21 -dependent molecular switch in Tn would have to await crystal structure data on Tn (see below).…”
Section: Skeletal and Cardiac Isoforms Of Troponinmentioning
confidence: 53%
See 1 more Smart Citation
“…The magnitude of change (K a of R162W is 2.6 times that of wild type) is similar to that observed between bisphosphorylated and dephosphorylated cTnI in a similar assay; however, the K a difference between the phosphorylated states is caused by a decreased k a (29). The binding of TnI and C is mediated via multiple interaction sites, with the N terminus of TnI binding to the C-terminal structural domain of TnC and the C terminus of TnI interacting with the N-terminal regulatory domain of TnC (9,10). The regulatory domain of cardiac TnC, in contrast to the skeletal muscle isoform, binds only one Ca 2ϩ ion via site II (site I is inactive) and this is sufficient for activation of the thin filament.…”
Section: Effect Of R145g and R162w Mutations On The Interaction Of Tnsupporting
confidence: 71%
“…The precise structure of the complex has yet to be elucidated, although the structure of isolated TnC is known (8). Low resolution studies and biochemical data have shown that TnI and TnC bind strongly to form an antiparallel dimer with multiple interaction sites (9,10).…”
Section: Familial Hypertrophic Cardiomyopathy (Hcm)mentioning
confidence: 99%